Urban vegetable production in Beijing, China: current progress, sustainability, and challenges - Li, Qiang; Yu, Zhou; Li, Mojun; Zhang, Guiqin; Lu, Tao; Li, Yang; Yu, Hongjun; Jiang, Weijie (Frontiers in Sustainable Food Systems, 2023)
Urbanization in China has entered a stage of accelerated development that is accompanied by a range of issues concerning resource, ecological and society. Urban vegetable production (UVP), an important part of urban agriculture, has the potential to be an effective countermeasure for dealing with these problems. Here, we review the current state of UVP with its related technology and equipment, and show the major models of UVP in China with three representative implementation cases in Beijing. Through this review, we found the impact of UVP on urban vegetable supply should not be underestimated, while it is still considered as an urban entertainment by public now. Moreover, UVP extension is still limited when compared with China’s urbanization process. We analyze the possible reasons that restrict the development of UVP and give corresponding suggestions to improve it. Considering the scale of urbanization in China, and the potential contribution of UVP to food supply, environmental sustainability and social harmony, there is still much room for UVP development, which will bring opportunities and challenges to the government and scientific researchers.